Analysis of Determinant Factors Influencing in Compliance Patient safety incident reporting Based on The Theory of Planned Behaviour - Alfi Yudisianto; Nurwijayanti; Prima Dewi (Ficco Public Health Journal, 2025)
Background: Patient safety is a priority for health services because it can cause serious public health problems. Incident reporting is essential to improve patient safety. This study aims to analysis of determinant factors influencing compliance patient safety incident reporting based on the theory of planned behaviour. Methods: This study used a cross-sectional design with the population being medical and nursing staff involved 116 participants who were determined using a simple random sampling technique. The analysis in this study used Logistic regression analysis. Results: the study found that health professionals mostly reported high bullying (56.9%), poor patient safety culture (75.0%), low protection motivation (53.4%), and non-compliance in reporting patient safety incidents (55.2%). Logistic regression analysis that had the potential to comply with incident reporting showed low bullying (aOR: 1.8; 95%CI: 0.69-4.81), good patient safety culture (aOR: 2.9; 95%CI: 093-9.25), and high protection motivation (aOR: 1.91; 95%CI: 0.86-4.25).). Conclusion: the importance of analyzing the determinant factors that influence compliance in reporting patient safety incidents is based on the theory of planned behavior, where low workplace bullying, good patient safety culture, and high protection motivation are the main determinants of compliance in reporting patient safety incidents.